2016
DOI: 10.1007/s11695-016-2061-z
|View full text |Cite
|
Sign up to set email alerts
|

Glucose Profiles in Pregnant Women After a Gastric Bypass

Abstract: This study is the first to describe CGM profile in pregnant women after RYGB. CGM features are similar to those of non-pregnant post-RYGB patients, characterized by wide and rapid changes in postprandial IG, and high exposure to hyperglycemia. The exposure to hyperglycemia is similar to what is reported in GDM although the time to postprandial peak is shorter. CGM could be an additional useful approach to screen for glucose intolerance during pregnancy after RYGB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 33 publications
1
21
0
1
Order By: Relevance
“…This effect was increased in the RYGB group during pregnancy (as an exaggerated insulin release was observed only during the OGTT and not during the IVGTT) and likely contributed to the high glycaemic variability seen after oral glucose administration. In line with our results, a recent study that used continuous subcutaneous glucose monitoring to evaluate glucose profiles in 35 bariatric pregnancies, suggested that abnormal glucose variability occurred in real-life conditions [35]. It is also worth noting that we found an exaggerated glucagon release immediately after glucose ingestion in the RYGB group.…”
Section: Discussionsupporting
confidence: 91%
“…This effect was increased in the RYGB group during pregnancy (as an exaggerated insulin release was observed only during the OGTT and not during the IVGTT) and likely contributed to the high glycaemic variability seen after oral glucose administration. In line with our results, a recent study that used continuous subcutaneous glucose monitoring to evaluate glucose profiles in 35 bariatric pregnancies, suggested that abnormal glucose variability occurred in real-life conditions [35]. It is also worth noting that we found an exaggerated glucagon release immediately after glucose ingestion in the RYGB group.…”
Section: Discussionsupporting
confidence: 91%
“…While a causal relationship between glycemic alterations and fetal development is obvious, we suggest that more detailed longitudinal examinations of glucose metabolism during pregnancy after GB would be essential to clarify this topic. Only one recent study using continuous subcutaneous glucose monitoring (CGM) in pregnant women with history of GB reported elevated postprandial glucose peaks followed by a rapid fall until 120 min after ingestion, suggesting considerable high amount of glucose variability in real-life conditions [20]. However, a detailed analysis of possible associations between glucose metabolism and fetal development was not provided in this study.…”
Section: Discussionmentioning
confidence: 86%
“…However, while those patients only had relatively lower glucose levels compared to controls, more than 50 % of pregnant gastric bypass women present with pronounced hypoglycemia in the OGTT [6,19]. Moreover, continuous glucose monitoring during pregnancy revealed that RYGB patients spend over 13 % of their time with blood glucose levels below 60 mg/dl [20]. A possible relation between fetal growth and glycemic dysregulation in mothers after GB surgery was also underlined by our previous study where glucose nadir and insulin response during an OGTT were associated with lower birth weight percentiles as well [17].…”
Section: Discussionmentioning
confidence: 98%